The Influence of Organizational Culture, Transformational Leadership, Organizational Support and Employee Competency on Employee Innovation, Organizational Commitment and Organizational Performance of Village-Owned Enterprises In Bali Province - Kadek Duwika; Ida Aju Brahmasari; Ida Aju Brahma Ratih (Jurnal Syntax Admiration, 2023)
This study aims to determine the effect of organizational culture, transformational leadership, organizational support and employee competence on employee innovation, organizational commitment and organizational performance of Village-Owned Enterprises (Badan Usaha Milik Desa) in Bali Province. The study population was 583 employees. Using the Slovin formula with a tolerance of 5%, the number of samples was 273 respondents. Test the model with Generalized Least Square Estimation (GLS), structural equation model analysis (SEM). The test results show that the model (fit) can be seen from the values of GFI, AGFI, TLI, CFI, RMSEA and CMIN / DF, which are 0.928, 0.912, 0.958, 0.967, 0.067 and 0.514 all within the range of expected values so that the model can received. The results showed that: 1). Organizational culture influences innovation, organizational performance, and does not affect organizational commitment. 2). Transformational leadership influences innovation, organizational commitment, and organizational performance. 3). Organizational support influences innovation, organizational commitment, and organizational performance. 4). Competence affects organizational performance, and does not affect organizational commitment. 5). Innovation has no effect on organizational performance. 6). Organizational commitment influences the performance of Village-Owned Enterprises.